Examination of a pre-exercise, high energy supplement on exercise performance - Hoffman, J.; Kang, J.; Ratamess, N.; Hoffman, M.; Tranchina, C. P.; Faigenbaum, A. (Journal of the International Society of Sports Nutrition, 2009)
The purpose of this study was to examine the effect of a pre-exercise high energy drink on reaction time and anaerobic power in competitive strength/power athletes. In addition, the effect of the pre-exercise drink on subjective feelings of energy, fatigue, alertness and focus was also explored.